THE EFFECT OF USING QUESTION-ANSWER RELATIONSHIP STRATEGY ON STUDENTS’ READING COMPREHENSION AT THE FIRST SEMESTER OF ENGLISH STUDY PROGRAM UNIVERSITY OF PASIR PENGARAIAN - Wirda Jannatul Jannah (ETERNAL (English, Teaching, Learning and Research Journal), 2022)
The purpose of this study is to find out whether there is or no significant effect of using Question-Answer Relationship Strategy on students’ Reading Comprehension at first semester students of English Study Program University of Pasir Pengaraian. This research was experimental research with a control group design. It involved 42 students in the first semester of the English Study Program University of Pasir Pengaraian. The data were collected using multiple-choice tests and two classes as the sample in this research. One class served as an experimental class and the other one as a control class. Both classes will give a pre-test and a post-test.The data was calculated by using Statistical Package for Social Science (SPSS) formula. The data were analyzed by Independent T-test with t-values was 6.156 with sig. p-value is 0.000 compare with t-table 5% (0.05) = 2.021. The finding showed that t-value6.156 ≥ t-table 5% (0.05) = 2.021. It meant the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. It could be concluded that there was a significant effect of using Question Answer Relationship strategy. QARs could improve students reading comprehension and it could be applied in teaching reading comprehension at first semester students of English Study Program University of Pasir Pengaraian